Gut microbiota and derived metabolomic profiling in glaucoma with progressive neurodegeneration - Zhang, Yinglei; Zhou, Xujiao; Lu, Yi (Frontiers in Cellular and Infection Microbiology, 2022)
Glaucoma is a multifactorial, neurodegenerative disorder characterized by the loss of retinal ganglion cells (RGCs). Crosstalk between the gut microbiota and host is involved in the progression of many neurodegenerative diseases, although little is known about its role in glaucoma. To investigated the alterations of the gut microbiota and derived metabolites in glaucomatous rats, and the interaction with RGCs, we performed 16S rRNA (V1-V9) sequencing and untargeted metabolomic analyses. The microbial composition differed significantly between the two groups, and the diversity of cecal bacteria was dramatically reduced in glaucomatous rats. The Firmicutes/Bacteroidetes (F/B) ratio, Verrucomicrobia phylum, and some bacterial genera (Romboutsia, Akkermansia, and Bacteroides) were dramatically increased in the glaucomatous rat model compared with the control, which showed negative correlation with RGCs. Untargeted metabolomic analysis identified 284 differentially expressed metabolites, and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis revealed considerable enrichment mainly in bile secretion pathways. The relationships among the metabolites enriched in the bile secretion pathway, differentially expressed cecal microbiota, and RGCs were investigated, and glutathione (GSH) was found to be negatively correlated with Bacteroides and F/B and positively correlated with RGCs. Reduced GSH level in the blood of glaucoma rats is further established, and was negatively correlated with Romboutsia and the F/B ratio and positively correlated with RGCs. This finding suggests the potential role of the gut microbiota and derived metabolites in glaucoma, and GSH, a major antioxidant metabolite, was related to their effects, indicating the potential for the development of gut microbiota-targeted interventions for glaucoma.